Antioxidant and Neuroprotective Effects of Seed Oils from Trichosanthes kirilowii and T. laceribractea in Caenorhabditis elegans: A Comparative Analysis and Mechanism Study - Wenqian Wang; Shan Li; Yunguo Zhu; Xianghuan Cui; Zhejin Sheng; Hongbing Wang; Zhou Cheng (MDPI AG, 2024)
Excess reactive oxygen species (ROS) can accelerate amyloid β (Aβ) aggregation and tau protein hyperphosphorylation in neuron cells, which further leads to neurodegenerative diseases such as Alzheimer's disease (AD). Therefore, there is an urgent need to find natural and safe antioxidants for preventing or treating such neurodegenerative diseases. The seeds of Trichosanthes kirilowii Maxim and T. laceribractea Hayata have long been used for medicinal and edible purposes in China. However, the antioxidant and neuroprotective activities and underlying mechanisms of their seed oils still remain unclear. Herein, we examine the antioxidant and neuroprotective effects of seed oils extracted from different germplasms, T. kirilowii (YNHH and SDJN) and T. laceribractea (ZJQT and SXHZ), on ROS levels and neuroprotective activities in C. elegans. The results demonstrated that the seed oils significantly reduced the ROS levels in C. elegans by 17.03-42.74%, with T. kirilowii (YNHH and SDJN) exhibiting significantly stronger ROS scavenging abilities than T. laceribractea (ZJQT and SXHZ). The seed oils from T. kirilowii (YNHH and SDJN) alleviated the production and aggregation of Aβ and the phosphorylation and polymerization of tau, suggesting a potential neuroprotective role. Conversely, seed oils from T. laceribractea (ZJQT and SXHZ) show minimal neuroprotective effects in C. elegans. These differential outcomes might stem from distinct mechanisms underlying antioxidant and neuroprotective effects, with the ctl-2 gene implicated as pivotal in mediating the significant neuroprotective effects of seed oils from T. kirilowii (YNHH and SDJN). Our findings have provided valuable insights into the antioxidant and neuroprotective properties of T. kirilowii seed oils, paving the way for further research aimed at elucidating the underlying mechanisms and exploring their potential therapeutic applications in combating neurodegenerative diseases.